Acute respiratory effects of exposure to ammonia on healthy subjects - Sundblad, Britt-Marie; Larsson, Britt-Marie; Acevedo, Fernando; Ernstgård, Lena; Johanson, Gunnar; Larsson, Kjell; Palmberg, Lena (Scandinavian Journal of Work, Environment & Health, 2004)
' ' OBJECTIVES ': 'This study investigated the acute respiratory effects of low ammonia exposure on healthy persons. ' ' METHODS ': 'Twelve healthy persons underwent sham or ammonia (5 and 25 ppm) exposure randomly in an exposure chamber on three occasions. The exposure duration was 3 hours, 1.5 hours resting (seated) and 1.5 hours exercising (50 W on a bicycle ergonometer). Symptoms were registered repeatedly before, during, and after the exposure on visual analogue scales. Bronchial responsiveness to methacholine, lung function, and exhaled nitric oxide (NO) were measured before and 7 hours after the exposure. In addition, nasal lavage was performed, and peripheral blood samples were drawn before and 7 hours after the exposure. ' ' RESULTS ': 'All the symptom ratings increased significantly during 25-ppm ammonia exposure as compared with the control exposure. The cumulative dose of methacholine causing a 20% decrease in forced expiratory volume in 1 second was lower (<1 concentration step of methacholine) for the exposure than for a pretrial control challenge. However, no difference was found between the control and ammonia exposures (P=0.33). The ammonia exposure did not significantly influence lung function or the exhaled NO levels. The total cell or interleukin-8 concentration in nasal lavage fluid did not change. The total leucocyte concentration in peripheral blood increased significantly (P<0.001) after both the sham and ammonia exposure, mainly due to an increase in neutrophils (P<0.001). Ammonia exposure did not significantly alter complement factor 3b in plasma. ' ' CONCLUSIONS ': 'During ammonia exposure in an exposure chamber, symptoms related to irritation and central nervous effects increase and are constant with no signs of adaptation. Ammonia inhalation does not cause detectable upper-airway inflammation or increased bronchial responsiveness to methacholine in healthy persons.
Keywords: acute respiratory effect; ammonia; bronchial responsiveness; exposure; human; inflammation; respiratory effect; symptom